(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This paper examines the scientific legacy of Mirzo Ulugbek and his contribution to the advancement of science through a historical-analytical lens. The objective of the study is to analyze the activities of the scientific school founded by Ulugbek and to interpret it from the perspective of a modern scientific management model. The research employed methods of historical source analysis, comparative analysis, and scientific generalization. The results demonstrate that the Samarkand Observatory served not only as a center for astronomical observation but also as a scientific school that systematically organized research activities. The scholarly environment established by Ulugbek was built upon the principles of strategic leadership, collaborative teamwork, and state support. This historical experience holds considerable theoretical and practical significance for contemporary scientific management systems.